Social Context and Perceived Belonging: A Comparative Study of Children of Immigrants in New York and Madrid - Sperling Smokoski, Jessica (2014)
This project examines the ways in which distinct contexts - and, specifically, distinct histories of immigration and ethnoracial diversity - affect the form, nature, and salience of boundaries demarcating an us/them (immigrant/non-immigrant) divide, including the perceived possibilities of social membership and the compatibility of minority and majority identity. It centers on the following research questions: What do the young adult 1.5/2nd generation see as the dominant boundaries or social divides in their countries of residence, in terms of differentiating immigrant-origin or ethnoracial minority groups from a perceived native-origin/mainstream population? How fluid are these boundaries, and when/why may they be subject to change? To what degree do children of immigrants feel receiving society national membership is available to them, and how does immigrant-origin or ethnoracial minority status play a role in in limiting (or, perhaps, permitting) membership? It examines these issues in a comparative perspective, focusing on young adult 1.5 and 2nd generation Dominicans and Colombians in New York City (a location with a historical immigrant presence) and Madrid (a location new to immigration). Methodologically, it utilizes 105 semi-structured in-depth interviews with individuals in these populations. By identifying the bases of, and barriers to, perceived possibilities of belonging in different social context, this project improves understanding of the current shape and possible future course of diversity in receiving societies